Efektivitas Program Sala Lauak dalam Optimalisasi Gerakan Indonesia Sadar Adminduk (GISA) Disdukcapil Kota Pariaman - Putri, Oky Marliani (JESS (Journal of Education on Social Science); Vol 5 No 2 (2021): The Role of Social Science in Overcoming Social IssuesDO - 10.24036/jess.v5i2.357, 2021)
This study aims to analyze the effectiveness of the Sala Lauak program in optimizing the GISA program and identify the factors that influence the effectiveness of the population document direct service program in Pariaman City and to find out the obstacles that occur during the implementation of the direct population document issuance service in Pariaman City. The method used is a descriptive method using a qualitative approach. The information used is primary and secondary information with data collection techniques carried out through interviews, observations, and documentation studies with informants of the Population and Civil Registration Office of Pariaman City and the people who receive services through the Sala Lauak program. The Sala Lauak program is a direct service for the issuance of population documents which is carried out to facilitate and bring service access closer to the community. The results of the study show that overall the program has been running well but not yet fully effective. This is because there are still obstacles related to the low understanding of citizens, lack of socialization, lack of discipline, lack of human resources, and internet network problems